Manajemen Ektrakurikuler untuk Mengembangkan Minat dan Bakat Siswa di Sma Negeri 2 Mendo Barat - Intan Juwita; Zulinka Manissha; Joko Supriyanto; Karmila Sari; Aang Praboyo; Peri Sagita; Suwardian Ramadhan; Audy Cahya Lestari; Oktarina Oktarina (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
This research discusses about the management of extracurricular activities in developing students' interests and talents in SMA Negeri 2 Mendo Barat. Extracurricular activities are educational activities outside the subject and counseling services to assist the development of students according to their needs, potential, interests, and talents through activities specifically organized by education or education staff who are capable and authorized in school. The purpose of this research was to determine extracurricular management in developing students' interests and talents. The method used in this research is descriptive qualitative. Data collection by observation, interview, documentation, and questionnaire. The research findings that extracurricular activities at SMA Negeri 2 Mendo Barat are required for all students and have been running well according to the provisions set by the school although there are still some obstacles in their implementation such as lack of experts in their fields, lack of facilities and infrastructure that support the implementation of activities, the lack of motivation from students so that there are still some students who do not follow extracurricular activities. In addition, the extracurricular activities that have just been active in SMA Negeri 2 Mendo Barat amounted to 8 extracurriculars, namely soccer, volleyball, scouting, rohis, 4 pillars of education, Taekwondo, KIR, PKS. The very limited number of extracurricular activities is one of the reasons students do not participate in extracurricular activities at school.